P06-20 Citidin Deaminase as a Predictive Biomarker of Antineoplastic Toxicity: Genotyping and Phenotyping - P. Castro-Sanchez; A. Corno Caparros; L. Pitaluga Poveda; A. Cardona Llorens; M.J. Prieto Castello; D. Marhuenda Amorós (Toxicology Letters, 2025)

Opportunities to better integrate inland fish and fisheries in multilateral environmental agreements - Abigail J. Lynch; Devin Bartley; T. Douglas Beard, Jr.; Gabriel Borba; Steven J. Cooke; Ian G. Cowx; Vittoria Elliott; Holly Embke; Edith Gondwe; Zeb Hogan; Jonathan G. Low; Jamie C. Madden; et al. (Environmental Science & Policy, 2025)

Comanagement and reconciling of ecological and economic benefits in an Amazonian freshwater fishery - Monalisa R. O. Silva; Leandro Castello; Carolina T. Freitas; João V. Campos‐Silva; Carlos A. Peres; Evlyn M. L. M. Novo (Conservation Biology, 2025)
Freshwater ecosystems contribute substantially to the global fish catch. However, freshwater fisheries face growing human pressures and are underrepresented in global analyses and conservation strategies. Attempts to reconcile conservation and human welfare goals in fisheries have led to comanagement by the government and local communities, along with other stakeholders, but assessments of its effectiveness in freshwater fisheries are lacking. We investigated the effectiveness of comanagement in freshwater fisheries by assessing ecological (fish catch) and economic (fishing revenue) outcomes in a major tributary of the Amazon Basin. Fisheries comanagement in the Amazon is typically implemented through an approach developed by riverine communities called lake management in which floodplain lakes are categorized as open access, subsistence, or protected. Each category has different levels and types of fishing pressure. We analyzed data (e.g., fishing data and management rules) from 1607 fishing trips of 198 fishers over 5 years in 30 riverine communities in 74 floodplain lakes (20 open access, 33 subsistence, and 21 protected). Lake comanagement increased fish catch in protected lakes over time by 12% (2.4 kg) compared with subsistence lakes and by 13% (2.6 kg) compared with open‐access lakes ( p = 0.03). Increased fish catch in protected lakes was mainly due to limits on fishing effort. Fishing revenue was 63% greater in protected lakes than in open‐access lakes ( p

A second update to the checklist of the vascular flora native to Italy - F. Bartolucci; L. Peruzzi; G. Galasso; A. Alessandrini; N. M. G. Ardenghi; G. Bacchetta; E. Banfi; G. Barberis; L. Bernardo; D. Bouvet; M. Bovio; G. Calvia; et al. (Plant Biosystems, 2024)

A second update to the checklist of the vascular flora alien to Italy - G. Galasso; F. Conti; L. Peruzzi; A. Alessandrini; N. M. G. Ardenghi; G. Bacchetta; E. Banfi; G. Barberis; L. Bernardo; D. Bouvet; M. Bovio; M. Castello; et al. (Plant Biosystems, 2024)

The stock assessment theory of relativity: deconstructing the term “data-limited” fisheries into components and guiding principles to support the science of fisheries management - Jason M. Cope; Natalie A. Dowling; Sybrand A. Hesp; Kristen L. Omori; Pia Bessell-Browne; Leandro Castello; Rowan Chick; Dawn Dougherty; Steven J. Holmes; Richard McGarvey; Daniel Ovando; Josh Nowlis; et al. (Reviews in Fish Biology and Fisheries, 2023)

The ten steps to responsible Inland fisheries in practice: reflections from diverse regional case studies around the globe - Steven J. Cooke; Elizabeth Nyboer; Abigail Bennett; Abigail J. Lynch; Dana M. Infante; Ian G. Cowx; T. Douglas Beard; Devin Bartley; Craig P. Paukert; Andrea J. Reid; Simon Funge-Smith; Edith Gondwe; et al. (Reviews in Fish Biology and Fisheries, 2021)

More nature in the city - G Capotorti; S Bonacquisti; L Abis; I Aloisi; F Attorre; G Bacaro; G Balletto; E Banfi; E Barni; F Bartoli; E Bazzato; M Beccaccioli; et al. (Plant Biosystems, 2020)

Fishery yields vary with land cover on the Amazon River floodplain - Leandro Castello; Laura L Hess; Ram Thapa; David G McGrath; Caroline C Arantes; Vivian F Renó; Victoria J Isaac (Fish and Fisheries, 2018)
Inland fisheries underpin food security in many tropical countries. The most productive inland fisheries in tropical and subtropical developing countries occur in large river–floodplain systems that are often impacted by land cover changes. However, few studies to date have assessed the effects of changes in floodplain land cover on fishery yields. Here, we integrated fisheries and satellite‐mapped habitat data to evaluate the effects of floodplain deforestation on fishery yields in 68 floodplain lake systems of the lower Amazon River, representing a wide range in relative amounts of woody, herbaceous and non‐vegetated land cover. We modelled relative fish yields (fish capture per unit effort [ CPUE ]) in the floodplain lakes as a function of the relative amounts of forest, shrub, aquatic macrophyte and bare/herbaceous habitats surrounding them. We found that forest amount was positively related ( p = .0003) to multispecies CPUE . The validity of these findings was supported by rejection of plausible alternative causative mechanisms involving habitat‐related differences in amount of piscivores, fishing effort, lake area, and habitat effects on CPUE of the nine taxa dominating multispecies yields. Our results provide support to the idea that removal of floodplain forests reduces fishery yields per unit effort. Increased protection of floodplain forests is necessary to maintain the food, income and livelihood security services provided by large river–floodplain fisheries.

Recovery of Arapaima sp. populations by community‐based management in floodplains of the Purus River, Amazon - T. A. Petersen; S. M Brum; F. Rossoni; G. F. V. Silveira; L. Castello (Journal of Fish Biology, 2016)
In the present study a unique dataset on population abundance in various community‐based management ( CBM ) and non‐ CBM areas is analysed to address the question of whether CBM can recover overexploited populations of Arapaima sp. in river‐floodplain ecosystems. All non‐ CBM areas possessed depleted Arapaima sp. populations with a mean density of 0·01 individuals ha −1 . Arapaima sp. population densities in all CBM areas changed over time from depleted to overexploited or well managed status, with a mean rate of increase of 77% year −1 . Rates of Arapaima sp. population recovery in CBM areas differed, probably reflecting differences in ecosystem productivity and compliance with management regulations. These results indicate that CBM schemes can be effective tools for the recovery and conservation of fish populations with non‐migratory life cycles in tropical river‐floodplain ecosystems.

Are Red Lists really useful for plant conservation? The New Red List of the Italian Flora in the perspective of national conservation policies - G. Rossi; C. Montagnani; T. Abeli; D. Gargano; L. Peruzzi; G. Fenu; S. Magrini; M. Gennai; B. Foggi; R.P. Wagensommer; S. Ravera; A. Cogoni; et al. (Plant Biosystems, 2014)

Erratum to: Modeling population dynamics and conservation of arapaima in the Amazon - L. Castello; D. J. Stewart; C. C. Arantes (Reviews in Fish Biology and Fisheries, 2012)

Modeling population dynamics and conservation of arapaima in the Amazon - L. Castello; D. J. Stewart; C. C. Arantes (Reviews in Fish Biology and Fisheries, 2011)

Nesting habitat of Arapaima gigas (Schinz) in Amazonian floodplains - L. Castello (Journal of Fish Biology, 2008)
Most nests of Arapaima gigas in floodplains of the Amazon were built at the margins of the forests surrounding temporary or permanent lakes and their connecting channels. They were found under forested levees in locations that were shallow and sandy. From 2000 to 2005, the adult population increased six‐fold but nest density increased only two‐fold.

A new method to distinguish the hyponatremia of electrolyte loss from that due to pure solvent changes - E. Bartoli; L. Castello; L. Bergamasco; P. P. Sainaghi (European Journal of Applied Physiology, 2007)

Winter precipitation on the US Pacific coast and El Niño–southern oscillation events - Amy F. Castello; M. L. Shelton (International Journal of Climatology, 2004)
Winter precipitation increases as much as seven times from south to north along the US Pacific coast. For 1948–95, nine coastal grid points are used to identify spatial and temporal winter precipitation variations and to assess atmospheric circulation influences on precipitation variability. A strong negative correlation to the northwest of each precipitation grid point is revealed by one‐point correlation maps of precipitation at a given coastal grid point and 700 hPa geopotential heights at 288 grid points. The strength of the correlation decreases from north to south, and the northernmost precipitation grid point displays a correlation pattern nearly opposite that of the southernmost precipitation grid point. El Niño events are related to greater than average precipitation south of 43°N along the US Pacific coast. The largest negative height anomalies during an El Niño year are centred over the North Pacific Ocean west of Oregon. La Niña events display an asymmetric pattern relative to El Niño, with below‐normal rainfall along the California coast south of 41°N and above‐normal precipitation along coastal Oregon and Washington. La Niña years have negative 700 hPa geopotential height anomalies over the Gulf of Alaska. These characteristics delimit the region between 41 and 43°N as the transition zone defining El Niño–southern oscillation influences along the US Pacific coast. Copyright © 2004 Royal Meteorological Society

Spatio-temporal distribution of seismic activity during the Umbria-Marche crisis, 1997 - A. Deschamps; F. Courboulex; S. Gaffet; A. Lomax; J. Virieux; A. Amato; A. Azzara; B. Castello; C. Chiarabba; G.B. Cimini; M. Cocco; M. Di Bona; et al. (Journal of Seismology, 2000)